Light Horse a history of Australia's mounted arm - Bou, Jean (Australian Army history series, 2010)
This book is a comprehensive history of the Australian Light Horse in war and peace. It examines the place of the Light Horse in Australia's military history throughout its existence, from its antecedents in the middle of the nineteenth century, until the disbandment of the last regiment in 1944.